Fleet verses Picoprep solution in bowel preparation for colonoscopy - Baharudin, Suraya; Sagap, Ismail; Y W, Yan; Md Nor, Azmi (2009)
We conducted this study to compare the effectiveness in bowel cleansing, side effects and electrolyte imbalance between Fleet and Picoprep in our population.